Acetone–butanol–ethanol production in a novel continuous flow system. (August 2015) - Elbeshbishy, Elsayed; Dhar, Bipro Ranjan; Hafez, Hisham; Lee, Hyung-Sool
Highlights: A novel continuous fermentation system with clarifier was used for ABE production. Mixed culture was used for ABE fermentation. Retention of ABE fermenters in the system improved ABE yield and production rate. Abstract: This study investigates the potential of using a novel integrated biohydrogen reactor clarifier system (IBRCS) for acetone–butanol–ethanol (ABE) production using a mixed culture at different organic loading rates (OLRs). The results of this study showed that using a setting tank after the fermenter and recycle the settled biomass to the fermenter is a practical option to achieve high biomass concentration in the fermenter and thus sustainable ABE fermentation in continuous mode. The average ABE concentrations of 2.3, 7.0, and 14.6 g ABE/L which were corresponding to ABE production rates of 0.4, 1.4, and 2.8 g ABE/Lreactor h were achieved at OLRs of 21, 64, and 128 g COD/Lreactor d, respectively. The main volatile fatty acids components in the effluent were acetic, propionic, and butyric acids. Acetic acid was the predominant component in the OLR-1, while butyric acid was the predominant acid in OLRs 2 and 3.